ANALYSIS OF PHONEMIC ERRORS TO IMPROVE ARABIC SPEAKING ABILITY - Nur Maya Badriatul Jamroh; Achmad Yani (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This research is motivated by the importance of mastering phonemes in Arabic speaking skills because pronunciation errors can change meanings, especially at Madrasah Diniyah Al Amiriyyah Blokagung Banyuwangi, where the students come from diverse linguistic backgrounds. The purpose of the research is to analyze the forms of phoneme errors, the underlying factors, and the corrective measures in the Language Community activities. Qualitative descriptive method with a field research design, data were collected thru in-depth interviews, participatory observations, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña, and validated thru source, technique, and time triangulation. The results show three main forms of phoneme errors: substitution (48%) such as [نشكر] pronounced as [نسكر] and [محبتي] becoming [مهبتي]; reduction (22%) such as [يستنون] pronounced as [يستنن]; and addition (4%) such as [الكتب] becoming [الكتوب]. Errors in tashdid and vowel length are also significant, with 9 and 10 occurrences respectively. The contributing factors include lack of interest and motivation, perception of Arabic as difficult, mother tongue interference (Javanese, Madurese, Osing), monotonous teaching methods, and an unconducive learning environment. It is concluded that phonemic errors are systematic and influenced by internal and external factors, thus requiring innovative strategies such as memorizing vocabulary thru songs, articulation practice with mirrors, educational games, and the creation of an intensive Arabic-speaking environment.